Baseline calculation of greenhouse gases emissions and future projections for the transport sector in the state of Veracruz, Mexico - Martínez-Rodríguez, María Concepción (2019)
Transport in the State of Veracruz-Mexico represents the third sector in energy consumption and the fastest growing emissions of Greenhouse Gases, the calculation of the baseline or trend scenario using the Long-range Energy Alternatives Planning system (LEAP) model in the period 2010-2026 reports a range of 10.3 million to 15.3 million tonCO2e tonCO2e respectively, arising from the consumption of gasoline and diesel mainly. The scenarios presented are related to the penetration of diesel vehicles and hybrid vehicles, use of ethanol fuel and reducing the use of private cars and trucks for passengers and cargo trucks. The momentum of these scenarios has the potential to reduce fuel emissions for the year 2026 in an amount equivalent to more than 15% of total emissions for the period 2010-2026.